PENGARUH PARAMETER BANGUNAN HIJAU GBCI TERHADAP FASE PROYEK - Edwin S. Wiyono; Enry L. Dusia; Ratna S. Alifen; Jani Rahardjo (Program Studi Magister Teknik Sipil - Petra Christian University, 2014)
Green building concept has been widely developed globally as well as in Indonesia. Green Building Council Indonesia (GBCI) is the institution that organizes the green building certification in Indonesia. The view from construction parties is needed to understand the level of interest and level of implementation of green building parameters and the impact of green building parameters on project life cycle time. This research carried out by distributing questionnaires to construction parties in Jakarta and Surabaya. Descriptive analysis and Structural Equation Modelling is used to understand the respondent views of the green building parameters and the impact of green building parameters on project life cycle time.The results showed that the level of interest of green building parameters is high. The comparison between level of importance and level of implementation shows that the implementation rate is lower than the importance rate. Water conservation is a significant aspect affecting the project life cycle time specifically the design stage, while the other aspects haven’t been significantly affecting project life cycle time.